Pemberdayaan Masyarakat Dalam Penanggulangan Stunting Di Kecamatan Banyuasin III Kabupaten Banyuasin - Vadia, Rani; Suryati, Suryati; Muzaiyanah, Muzaiyanah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Community empowerment in tackling stunting in Banyuasin III District, Banyuasin Regency is an activity carried out by the sub-district government and village midwives for stunting sufferers with the aim that the community can be empowered and stunting sufferers can be reduced so that there are no more stunting sufferers in the sub-district. This research is focused on the background, namely the first What is the community's strategy in overcoming stunting in Banyuasin III District. Second, what are the obstacles to community empowerment in overcoming stunting in Banyuasin III District. The purpose of this study is to find out the stages of community empowerment in overcoming stunting in Banyuasin III District, Banyuasin Regency. This study used a qualitative method of field research. The subjects of this study were three stunting sufferers and two village midwives. The data collection techniques used by researchers are observation methods, interview methods and documentation methods. The data analysis technique is using data reduction, data presentation and conclusion drawing. The results of the study show that community empowerment in tackling stunting in Banyuasin III District, Banyuasin Regency through two stages. First, the Awareness Stage, namely by socialization, and the Intellectual Capability Improvement Stage, skills and skills so that initiatives and innovative abilities are formed to deliver a pattern of independence, an independent society. cannot be left alone, the community still needs protection as monitored by posyandu. Community empowerment in tackling stunting is said to be successful, because with this program the stunting rate can be reduced in the coming year, and the community already understands a clean and healthy lifestyle.